Towards sustainable productivity enhancement of rice-based farming systems in sub-Saharan Africa - Rodenburg, J.; Saito, Kazuki (Elsevier, 2022)
In the past 50 years, rice has become an important crop for food security in sub-Saharan Africa. However, rice yields remain relatively low, and large yield gaps exist. This Special Issue brings together agronomy research on rice-based farming systems in sub-Saharan Africa and addresses three main, overarching questions: (1) what has been achieved in the past decades in terms of rice agronomy in sub-Saharan Africa, (2) what is the state-of-the-art regarding development of technologies and (3) what will be likely or required future directions? The broad topics included in this Special Issue are (1) yield trends and yield gap analyses, (2) soil & nutrient, water, weed and integrated crop management practices, (3) cropping systems, (4) genetic improvements, (5) crop simulation modeling, and (6) assessment of farmers’ rice cultivation practices and the sustainability of these practices. The papers cover different sub-regions, from the Sahel to the highlands of Madagascar and three major rice growing environments (irrigated lowlands, rainfed lowlands, and rainfed uplands). In this paper we describe the major challenges in the rice production sector in sub-Saharan Africa and historical efforts on agronomy research, and we provide a short introduction and discussion on the papers presented in this Special Issue. This Special Issue arrives at six main recommendations. 1. There is a need to increase research and development efforts focusing on rainfed rice-based systems. 2. More attention needs to be paid to research on the farming system or landscape level, aimed at development of integrated cropping and farming systems and integrated agronomic solutions. 3. Current and future agronomic rice research should thematically center around sustainability, including judicious natural resources management, climate change adaptation and mitigation, and conservation of biodiversity and environments. 4. To operationalize this, sustainability performance indicators need to be developed and used. 5. There is broad consensus regarding the need for more labor-saving technologies, including mechanization options, provided these do not increase the ecological footprint of production systems. 6. Future rice agronomy research work should be interdisciplinary and transdisciplinary, to better address the myriad of challenges of smallholder farmers in Africa. Papers presented in this Special Issue should inform on the state-of-the art in rice agronomy in SSA, and on ways to sustainably enhance rice production and self-sufficiency in this region